"The Missing Link": The Tubulin Mutation Database Connects Over 1500 Missense Mutations With Phenotypes Across Eukaryotes. Issue 2 (4th April 2019) - Hussey, Shane P; Fritz‐Laylin, Lillian K
Abstract : As outlined in their recent paper (A Tubulin Mutation Database: A Resource for the Cytoskeletal Community), Catherine Pham and Naomi Morrissette from the University of California, Irvine, scoured the literature and catalogued data for 489 point mutations for 𝛂‐tubulin, 729 for β‐tubulin, and 343 for 𝛄, ẟ, 𝛆, and 𝛇 tubulins to create the tubulin mutation database (http://tubulinmutations.bio.uci.edu ). The database is a searchable catalog of missense mutations and phenotypes that is expected to grow with biannual updates. Data entries regarding the species and isoform, as well as links to available sequences and the original study which characterized the mutant are intuitively displayed and color coded (Pham & Morrissette, 2019). This database represents a unique opportunity for clinicians and cell biologists to rapidly connect sequence data to mutant phenotypes and gather primary literature which promises to facilitate discoveries on topics including microtubule dynamics, antimitotic drug use and resistance, and evolution. We expect that many researchers will find this tool of great use to their research. This article is protected by copyright. All rights reserved.